Rheumatic Heart Disease: Molecules Involved in Valve Tissue Inflammation Leading to the Autoimmune Process and Anti-S. pyogenes Vaccine - Guilherme, Luiza; Kalil, Jorge (Frontiers in Immunology, 2013)
The major events leading to both rheumatic fever and rheumatic heart disease are reviewed. Several genes are involved in the development of rheumatic fever (RF) and rheumatic heart disease (RHD). The inflammatory process that results from S. pyogenes infection involves the activation of several molecules such as VCAM and ICAM, which play a role in the migration of leukocytes to the heart, particularly to the valves. Specific chemokines, such as CXCL3/MIP1α as well as CCL1/I309 and CXCL9/Mig, attract T cells to the myocardium and valves, respectively. The autoimmune reactions are mediated by both the B- and T-cell responses that begin at the periphery, followed by the migration of T-cell clones to the heart and the infiltration of heart lesions in RHD patients. These cells recognize streptococcal antigens and human tissue proteins. Molecular mimicry between streptococcal M protein and human proteins has been proposed as the triggering factor leading to autoimmunity in RF and RHD. The production of cytokines from peripheral and heart-infiltrating mononuclear cells suggests that T helper 1 (Th1) and Th17 cytokines are the mediators of RHD heart lesions. The low numbers of IL-4-producing cells in the valvular tissue might contribute to the maintenance and progression of the valve lesions. The identification of a vaccine epitope opens a perspective of development of an effective and safe vaccine to prevent S. pyogenes infections, consequently RF and RHD.